PROBLEMATIKA PENGAWASAN BANK PERKREDITAN RAKYAT SYARIAH DI PAMEKASAN - Zainal Abidin (Institut Teknologi Sepuluh Nopember, 2012)
DPS It is urgent to give serious respond on the existing opinion that syariahbanking is practically similar to conventional one. In fact, they are differentin certain folds. One of the distinctive points is that the former has beenequipped by a supervision board—Dewan Pengurus Syariah (DPS). Thisarticle exposes two things: firstly, it discusses how DPS operates itssupervision function against BPR Syariah SPM in Pamekasan; secondly, itdescribes how DPS contributes its supervision function toward BPR SyariahSPM Pamekasan as an effort to keep the BPR Syariah be in the syariah(Islamic law) track. This research employs case study design of qualitativeapproach. This study results the followings—firstly, DPS has systematicallysupervised the BPRS SPM. The supervision is regularly undergone at leastonce a month toward the administration (contract transaction) and customer.Secondly, DPS BPRS SPM runs important contribution to enhance thesyariah values of BPRS SPM. DPS both supervise and advise BPRS SPM touphold the syariah principles in running the whole banking operations.